2015
DOI: 10.1055/s-0035-1553269
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Cardiac Axis in Fetuses with Conotruncal Anomalies

Abstract: The purpose of this study was to assess the cardiac axis in fetuses with conotruncal anomalies during four-chamber view scanning. We retrospectively evaluated the cardiac axis of 150 fetuses with conotruncal anomalies within the second and third trimester between October 2008 and August 2014. The cardiac axis was obtained by the angle of two lines in a transverse view of the fetal thorax at the level of the four-chamber view. The first line divided the thorax into two equal halves starting from the spine poste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…However, this might hold true, as primary detection of congenital cardiac anomalies is poor according to the German screening program "Mutterschaftsrichtlinien", especially for conotruncal anomalies which might not be easily detectable within the 4-chamber view. But with more training for the basic examiner, we showed before that careful evaluation of the fetal cardiac axis at 18-22 wks could be a useful screening tool for better prenatal detection of conotruncal anomalies like TOF, because of the frequent leftward rotation of the cardiac axis in those cases [15].…”
Section: Discussionmentioning
confidence: 98%
“…However, this might hold true, as primary detection of congenital cardiac anomalies is poor according to the German screening program "Mutterschaftsrichtlinien", especially for conotruncal anomalies which might not be easily detectable within the 4-chamber view. But with more training for the basic examiner, we showed before that careful evaluation of the fetal cardiac axis at 18-22 wks could be a useful screening tool for better prenatal detection of conotruncal anomalies like TOF, because of the frequent leftward rotation of the cardiac axis in those cases [15].…”
Section: Discussionmentioning
confidence: 98%
“…An abnormal fetal cardiac axis can point towards CHD and promote an early diagnosis [40][41][42][43]. A recent analysis was able to demonstrate that the cardiac axis is significantly different from the normal axis in conotruncal anomalies (DORV, TAC, and TOF) [45]. Additionally, the study showed that in…”
Section: Discussionmentioning
confidence: 93%
“…Initial measurements were used in all analyses. Finally, the heart axis was measured in the four-chamber view as described in the ISUOG guidelines [ 25 ], as other studies showed an abnormal heart axis can be associated with an RAA [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%